2000
DOI: 10.1111/j.1834-7819.2000.tb00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies of dental root surface caries 2: The role of cementum in root surface caries

Abstract: Artificial caries lesions were produced in roots of teeth using an acetate buffer system, when the layer of cementum was either normal in thickness, excessively thickened by hypercementosis, or had been removed completely. The rates of lesion progression were measured in each case using polarized light microscopy to measure lesion depth. Analysis of calcium (Ca) and phosphorus (P) loss during the demineralizing process was carried out. The removal of cementum was found to significantly increase the initial rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 7 publications
1
14
0
1
Order By: Relevance
“…This confirms the findings of McIntyre et al [2000b], although the difference was much less than they reported, and deeper lesions were not found on all root surfaces. McIntyre et al [2000b] suggested that removal of the cementum layer accelerated the initial rate of lesion progression, and that the rate was subsequently the same as on the intact surfaces. This suggestion is supported by the fact that, in the present study, at all pI HA /pH, the groups showed similar mean differences between the ground and intact surfaces.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This confirms the findings of McIntyre et al [2000b], although the difference was much less than they reported, and deeper lesions were not found on all root surfaces. McIntyre et al [2000b] suggested that removal of the cementum layer accelerated the initial rate of lesion progression, and that the rate was subsequently the same as on the intact surfaces. This suggestion is supported by the fact that, in the present study, at all pI HA /pH, the groups showed similar mean differences between the ground and intact surfaces.…”
Section: Discussionsupporting
confidence: 80%
“…as pI HA increased). The mechanism proposed by McIntyre et al [2000b] for cementum removal affecting only initial demineralization rate is not very convincing. A simpler explanation for a uniform difference is that the process of grinding off the cementum creates a smear layer and a subsurface region of mechanical damage which are more vulnerable to dissolution.…”
Section: Discussionmentioning
confidence: 99%
“…In the buffer system however cementum removal 20 who showed that cementum can protect the underlying dentine from demineralisation. Although both tissues react similarly to an acid challenge, 21,22 the matrix of cementum is less permeable than that of dentine and may retard transport processes in demineralisation.…”
Section: Effect Of Cementum Removal (Studies a And B)mentioning
confidence: 96%
“…Smooth (buccal and lingual) coronal and root surfaces are more readily exposed to saliva's remineralizing potential than are proximal surfaces and occlusal fissures. Additionally, because the critical pH for demineralization is higher for dentin than it is for enamel (Fejerskov and Kidd, 2008), root surfaces are considered to be at a higher caries risk than coronal surfaces (McIntyre et al, 2000). Therefore, when one is studying the effectiveness of interventions on caries prevention, it is important to examine their effects on these different tooth surfaces as a whole as well as separately (McDonald and Sheiham, 1992).…”
Section: Introduction Dmentioning
confidence: 99%